PENGELOLAAN BUMN SEBAGAI TRANSFORMASI KEUANGAN PUBLIK MENJADI KEUANGAN PRIVAT DALAM PERSEPEKTIF HUKUM KEUANGAN NEGARA - Darmawn, Agus (Yustitia, 2020)
The research aims to find the right perspective in the legal accountability of State-owned enterprises management. This research uses a normative approach. The results show that the national legal regulations have not provided clarity in regulations in the management of State-owned enterprises. The transformation of public finance into private finance is the key and clear line of demarcation to understand State-owned enterprises management in the perspective of state financial law, thereby fostering high confidence for Directors in managing State-owned enterprises in the principles of Good Corporate Governance